Characterization and Modeling of the Ratcheting Behavior of the Ferritic-Martensitic Steel P91 - Zhang, Kuo (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2017)
In this work, the ratcheting-behavior of 9%Cr-1%Mo ferritic-martensitic steel is studied with uniaxial cyclic loading. To describe the ratcheting-behavior of this steel, a visco-plastic constitutive model with consideration of cyclic softening of Reduced Activation Ferritic Martensitic steels is further modified, based on the analysis of back stress.